La généalogie de la nationalité : le caipira sous la plume de Valdomiro Silveira - Célia Regina Da Silveira (Caravelle)
This article analyzes the construction of the caipira’s representation in the São Paulo’s state, worked up by intellectuals at the end of the 19th century and the beginning of the 20th, as an ideal ethnic and cultural type to represent the Brazilian nation. This analysis is based upon paulista regionalist litterature, and deals particularly with the works of the writer Valdomiro Silveira.